Screening as a Cancer Control Strategy - Szklo, Moysés (2018)
In addition to primary prevention, screening (early detection) is an important strategy for cancer control. In this paper, we summarize the major tenets of screening in general and use prostate and colorectal cancer as examples of the application of these tenets.